Intraluminal diamond‐like carbon coating with anti‐adhesion and anti‐biofilm effects for uropathogens: A novel technology applicable to urinary catheters. (4th September 2021) - Watari, Shogo; Wada, Koichiro; Araki, Motoo; Sadahira, Takuya; Ousaka, Daiki; Oozawa, Susumu; Nakatani, Tatsuyuki; Imai, Yuichi; Kato, Junichi; Kariyama, Reiko; Watanabe, Toyohiko; Nasu, Yasutomo
Abstract : Objectives: To examine anti‐adhesion and anti‐biofilm effects of a diamond‐like carbon coating deposited via a novel technique on the inner surface of a thin silicon tube. Methods: Diamond‐like carbon coatings were deposited into the lumen of a silicon tube with inner diameters of 2 mm. The surface of the diamond‐like carbon was evaluated using physicochemical methods. We used three clinical isolates including green fluorescent protein‐expressing Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus . We employed a continuous flow system for evaluation of both bacterial adhesion and biofilm formation. Bacterial adhesion assays consisted of counting the number of colony‐forming units and visualization of adhered bacterial cells by scanning electron microscope to evaluate the diamond‐like carbon‐coated/uncoated samples. The biofilm structure was analyzed by confocal laser scanning microscopy on days 3, 5, 7 and 14 for green fluorescent protein‐expressing Pseudomonas aeruginosa . Results: The smooth and carbon‐rich structure of the intraluminal diamond‐like carbon film remained unchanged after the experiments. The numbers of colony‐forming units suggested lower adherence of green fluorescent protein‐expressing Pseudomonas aeruginosa and Escherichia coli in the diamond‐like carbon‐coated samples compared with the uncoated samples. The scanning electron microscope images showed adhered green fluorescent protein‐expressing Pseudomonas aeruginosa cells without formation of microcolonies on the diamond‐like carbon‐coated samples. Finally, biofilm formation on the diamond‐like carbon‐coated samples was lower until at least day 14 compared with the uncoated samples. Conclusions: Intraluminal diamond‐like carbon coating on a silicone tube has anti‐adhesion and anti‐biofilm effects. This technology can be applied to urinary catheters made from various materials.